A Study on Assessment of Carbon Absorption Footprint (CAF) and Forestation in Local Governments - Soon Gil Kwon; Junbeum Kim; Seungjun Jeon (대한환경공학회지, 2023)
Purpose At the national level, carbon absorption during the carbon neutrality goal plays an important role, and related forestry projects are continuously increasing. Until now, forest carbon absorption has been measured and managed in various ways at the national level, but specific carbon absorption indicators for each local government have not been approached in various ways. Accordingly, the carbon absorption footprint (CAF) was defined, and the carbon absorption amount and carbon absorption rate were calculated and analyzed to compare and analyze the current situation for each region. Methods As for the research method in this study, standard carbon absorption by tree species was matched on the basis of age level per forest area nationwide as of 2020, and the carbon absorption amount of metropolitan governments, the carbon absorption amount of 250 basic local governments, the carbon absorption amount per national land area, And the carbon absorption footprint per forest area was calculated. Afterward, the carbon absorption rate for the national land area and the carbon absorption rate for the forest area of the basic local governments were calculated. Results and Discussion As a result of the study, the region with the highest amount of carbon absorption was in the order of Gangwon-do, Gyeongsangbuk-do, and Jeollanam-do, and the lowest carbon absorption was in the order of Gwangju Metropolitan City, Sejong Special Self-Governing City, and Daejeon Metropolitan City. Hongcheon-gun, Inje-gun, and Pyeongchang-gun in Gangwon-do had the highest absorption among basic local governments, followed by Yeongdeungpo-gu in Seoul, Dong-gu in Incheon, and Jung-gu in Busan in order of lowest. Seongbuk-gu, Gwangju-si, and Dong-gu, Daejeon were the basic local governments with a high absorption rate compared to the national land area, followed by Yeongdeungpo-gu, Dong-gu, Incheon, and Seongdong-gu, Seoul, respectively. Lastly, basic local governments with a high carbon absorption rate compared to forest areas were in the order of Seongbuk-gu in Seoul, Ulju-gun in Ulsan, and Hongcheon-gun in Gangwon-do, and Seongdong-gu, Gangdong-gu, and Dongjak-gu in Seoul were in the order of low rates. Overall, a lot of carbon was absorbed in Gangwon-do and Gyeongsangbuk-do, but when approaching the absorption ratio to the national area, on the contrary, Seoul, Gyeonggi, and Incheon showed high absorption rates. The ratio of carbon absorption to forest area was uniform across the country. Conclusion Based on this study, continuous research is needed to develop a forest creation scenario and achieve more carbon absorption. Since carbon absorption fluctuates greatly depending on forest management, it is considered that it will be an important indicator in terms of strategy presentation in afforestation or sink planning in the future for metropolitan or basic local governments.